Solid waste management service chain and sanitation safety: a case study of existing practice in Addis Ababa, Ethiopia - Sisay, Shegaw Fentaye; Gari, Sirak Robele; Ambelu, Argaw (Frontiers in Environmental Engineering, 2024)
Background: Poor sanitation safety in municipal solid waste management can cause environmental and public health problems. This is the case in Ethiopia, where the sanitation safety standards are low in the municipal solid waste management operations. Therefore, the sanitation safety practices along the solid waste management service chains in Addis Ababa, Ethiopia are poorly understood, and this research will contribute new insights for the scientific community and can also inform policies and the current solid waste management operations in Addis Ababa. related to unsafe waste storage, failure to properly store wastes at the household level, having safe storage practices, and unsafe waste segregation and storage.The study also examined the association between sanitation safety practices and sociodemographic factors using multiple linear regression analysis. Marital status, education, occupation, and income were found to be significant factors influencing sanitation safety practices during onsite waste handling. Income and marital status had the highest contribution, while occupation had the lowest contribution.: the research findings highlight the wide variation in sanitation safety practices and risks associated with solid waste management. The study emphasizes the need for improved waste management practices at the household level, waste collection and transport sites, transfer stations, and waste treatment/disposal sites. The identified risk factors should be addressed through targeted interventions, including public awareness campaigns, proper training of waste management workers, and the implementation of safety protocols and infrastructure improvements. Additionally, sociodemographic factors play a role in determining sanitation safety practices, emphasizing the importance of considering these factors when developing waste management strategies and interventions.